Resection of a Rare Metacarpal Distal Condyle Osteoid Osteoma - Bachar El Fatayri; Az-Eddine Djebara; Alex Fourdrain; Yassine Bulaid; Mario Sanguina (Case Reports in Orthopedics)
Introduction. Osteoid osteoma is a benign bone-forming tumor with young male predilection. It occurs predominantly in the long bones. In the hand, osteoid osteoma is more commonly located in the phalanges and carpal bones. The metacarpals are the least common site for osteoid osteoma. Pain is the most common symptom. It usually increases at night and responds to nonsteroidal anti-inflammatory drugs. Case Presentation. The authors report the excision of an osteoid osteoma lying at the distal condyle of a metacarpal bone of the left hand. The clinical and radiological findings are exposed as well as the surgical management of the lesion. Pain and swelling disappeared after surgery, and there was no evidence of recurrence at follow-up. Discussion. They discuss this rare location and further radiological examination that was used leading to the diagnosis. The imputation of the traumatic factor has been discussed, along with the different therapeutic possibilities and the advantages of a total excision while preserving the integrity of the adjacent ligament and joint space. Conclusion. The surgical alternative appears to be a satisfying treatment for osteoid osteoma in this particular superficial location. Both the exact pathogenesis and the contribution of the traumatic factor remain unclear.